Social media : a critical introduction - Christian Fuchs (Sage, 2014)
"Now more than ever, we need to understand social media - the good as well as the bad. We need critical knowledge that helps us to navigate the controversies and contradictions of this complex digital media landscape. Only then can we make informed judgments about what's happening in our media world, and why. Showing the reader how to ask the right kinds of questions about social media, Christian Fuchs takes us on a journey across social media, delving deep into case studies on Google, Facebook, Twitter, WikiLeaks and Wikipedia. The result lays bare the structures and power relations at the heart of our media landscape." -- Publisher's description.